Meningkatkan Hasil Belajar Siswa pada Pelajaran PKN dengan Menggunakan Tipe Jigsaw Materi Nilai-Nilai yang Terkandung dalam Pancasila pada Siswa Kelas IV SDN 113 HAL-SEL - Sufri Saleh; Rachmatia Tauhid; Iswan E. Tawari; Harzlina Udin (Jurnal Ilmiah Wahana Pendidikan, 2022)
This type of research is classroom action research (CAR), classroom action research. The research was carried out in class IV SDN 113 Hal-Sel. This research was carried out from June to July 2020. The subject of the research was class IV SDN 113 Hal-Sel which collected 20 students consisting of 13 male students and 7 female students). In the first cycle the average value was 59.25 or increased after improvements in the first cycle to 11 students who completed 55%. In the second cycle the average value of students became 66.75 the number of students increased to 95%. Based on data analysis, it is known that Civics lessons using the jigsaw method in the material values ​​contained in Pancasila have been successful. learning takes place very conductively and interactively students seem happy to learn Civics material values ​​contained in Pancasila. This can be seen from the students' learning outcomes which can be seen in their complete learning, the number of students who have completed has reached 95 (19 students who completed).